2017
DOI: 10.1016/s0140-6736(17)31585-4
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide once weekly versus placebo in Parkinson's disease: a randomised, double-blind, placebo-controlled trial

Abstract: Summary Background Exenatide, a glucagon-like peptide-1 (GLP-1) receptor agonist, has neuroprotective effects in preclinical models of Parkinson’s disease. We investigated whether these effects would be apparent in a clinical trial. Methods In this single-centre, randomised, double-blind, placebo-controlled trial, patients with moderate Parkinson’s disease were randomly assigned (1:1) to receive subcutaneous injections of exenatide 2 mg or placebo once weekly for 48 weeks in addition to their regular medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
467
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 616 publications
(510 citation statements)
references
References 37 publications
15
467
3
3
Order By: Relevance
“…However, studies in humans have not supported the use of GLP-1 RA in cerebral diseases (19), except for one clinical trial of 48 weeks, which suggested that exenatide once weekly had positive effects in Parkinson's disease, which were sustained beyond the period of exposure (20). Whether the exenatide therapy affects the underlying disease pathophysiology or the result simply is secondary to long-lasting metabolic improvements is uncertain.…”
mentioning
confidence: 99%
“…However, studies in humans have not supported the use of GLP-1 RA in cerebral diseases (19), except for one clinical trial of 48 weeks, which suggested that exenatide once weekly had positive effects in Parkinson's disease, which were sustained beyond the period of exposure (20). Whether the exenatide therapy affects the underlying disease pathophysiology or the result simply is secondary to long-lasting metabolic improvements is uncertain.…”
mentioning
confidence: 99%
“…GLP-1 receptor agonists increase insulin sensitivity and are neuroprotective in animal models of AD, PD, and stroke (Li et al, 2009, 2010; Liu et al, 2015b). A recent clinical trial revealed a therapeutic benefit of the GLP-1 analog exanatide in PD patients (Athauda et al, 2017). Metformin, which has been prescribed for diabetes for decades, inhibits liver glucose production, but also activates multiple cellular pathways that counteract aging processes, including activation of AMPK and inhibition of mTOR and inflammatory pathways (Barzilai et al, 2016).…”
Section: Metabolic Factors Can Accelerate or Decelerate Brain Agingmentioning
confidence: 99%
“…Currently, multiple GLP-1R agonists are indicated for the treatment of T2D, and liraglutide is also approved for obesity; however, indications such as nonalcoholic steatohepatitis, Parkinson's disease, and Alzheimer's disease are being explored. Indeed, several randomized controlled clinical trials have demonstrated significant clinical improvement in human subjects with Parkinson's disease (93). Despite the appeal of current GLP-1R agonists for the treatment of T2D, market penetration for many GLP-1R agonists remains disappointing, raising questions about the potential clinical classes used for treatment of T2D, the GLP-1R agonists and SGLT-2 inhibitors, produce weight loss, effective reduction of A1c, a low incidence of hypoglycemia, and reductions in rates of major adverse cardiovascular events and cardiovascular death (75,87).…”
Section: Glps: Current Use and Future Considerationsmentioning
confidence: 99%